2015
DOI: 10.2965/jwet.2015.371
|View full text |Cite
|
Sign up to set email alerts
|

Application of Stable Nitrogen Isotopes to Identify Nitrogen Sources in the Outflow Waters from a Paddy Field

Abstract: The increasing demand of rice crops leads to elevated levels of nitrogen in water bodies in Asia. The concentrations of organic and inorganic nitrogen and the nitrogen isotope ratio in nitrate (NO 3 -) were analysed to identify the sources of nitrogen in the outflow waters from a paddy field in Japan in 2013. Nitrogen concentrations in the drainage and percolation waters were the highest during the paddling period, NO 3 -was the dominant form of dissolved total nitrogen and the δ 15 N-NO 3 -values in both type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Concentrations of ammonium nitrogen (NH4-N) and nitrate nitrogen (NO3-N) in water samples were measured using an ion chromatography in the environmental laboratory at University of Yamanashi, Japan. The nitrogen stable isotope values of NH4-N (δ 15 N-NH4) and NO3-N (δ 15 N-NO3) in the water samples were measured by diffusion method [1] and microbial denitrified method [9], respectively, when the samples contained over 1.0mg/L of NH4-N and 0.05mg/L NO3-N. The δ 15 N in fertilizer samples was also measured by using elemental analyzer mass spectrometer [9].…”
Section: A Subjects and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of ammonium nitrogen (NH4-N) and nitrate nitrogen (NO3-N) in water samples were measured using an ion chromatography in the environmental laboratory at University of Yamanashi, Japan. The nitrogen stable isotope values of NH4-N (δ 15 N-NH4) and NO3-N (δ 15 N-NO3) in the water samples were measured by diffusion method [1] and microbial denitrified method [9], respectively, when the samples contained over 1.0mg/L of NH4-N and 0.05mg/L NO3-N. The δ 15 N in fertilizer samples was also measured by using elemental analyzer mass spectrometer [9].…”
Section: A Subjects and Methodsmentioning
confidence: 99%
“…Dissolved nitrogen is the main form of nitrogen (50 to 80% of total nitrogen) in ponded water [8] and, among the dissolved nitrogen compounds, nitrate accounts for 48-92% of total nitrogen losses in runoff water [12]. Previous studies reported the observed isotope value of nitrate in drainage and percolation water at the outlet of paddy fields [9], in which the irrigation water was supposed to be one of the nitrogen sources in drainage water and nitrate in percolation water was microbiologically affected. Nitrogen isotope value possibly changes during a cropping season because of the transportation and/or transformation processes and differs based on regional characteristics such as hydrometeorological conditions and agricultural practices [7].…”
Section: Introductionmentioning
confidence: 99%
“…Then 0.15 g of MgO was added to keep the sample solution basic (pH~9. 7) and to convert NH 4 + into NH 3 . A glass filter, pre-treated by combustion and containing 25 μL of 2 M sulfuric acid, was placed in a polyethylene container and suspended in the air space of the capped glass vial.…”
Section: Methodsmentioning
confidence: 99%
“…The isotope tracer technique is a useful tool for analysing the sources and fate of nitrogen in water environments. The use of the stable isotope ratio of nitrate dissolved in water has been extensively studied . In addition to the nitrate isotope ratio method, the application of stable isotope tracing to ammonium nitrogen is needed to understand the nitrogen cycle and nitrogen contamination.…”
Section: Introductionmentioning
confidence: 99%
“…The outputs of these models were the predicted water quality parameters, such as dissolved oxygen DO, ammonium NH 4 + , nitrite NO 2 − , nitrate NO 3 − and phosphate PO 4 3− , in streams, however, simulated outputs from such models are still uncertain without calibration and validation steps. This study focused on the application of the SWAT model to simulate discharge and transport processes of dissolved total nitrogen (DTN), which is the most important N form [35] and available data in this region, from point and nonpoint sources in a river basin with complex anthropogenic pollution sources. The purpose of this study is to assess the potential of applying the SWAT model to estimate nutrient loads to river basins in Vietnam.…”
Section: Introductionmentioning
confidence: 99%